THE ROLE OF DHAKA'S COMMUNITY-BASED PARKS IN IMPROVING CHILDREN’S MENTAL AND PHYSICAL HEALTH (Journal of Event, Tourism and Hospitality Studies, 2024)
This study focused on the significance of Community Park for enhancing children’s mental and physical health at the grassroots level of the community of Dhaka city. To assess the practical scenario both primary and secondary data was used in this study. Convenience sampling techniques have been applied to collect data with a pre-designed structured questionnaire. To reach the study goal, regression analyses have been applied to see the correlation between children’s health and community park activities. Furthermore,categorized the impact to understand the vulnerability. The evidence identified that such community park contributes significantly to children's physical and mental well-being, fostering a positive impact on their holistic development. The study findings demonstrated that ∼ 80% of children think community parks significantly contribute to maintaining their mental wellbeing. Similarly, 61% of children expressed that park activities reduce their stress and anxiety. In addition, regular activities impact on their physical growth which was expressed by 90% of respondents. The result also finds out a strong correlation between the physical and mental health of the children. In addition, it analyzed the correlation of impact between their education and health. Besides, the study also assesses the levels of severity of depression, anxiety, and sleeping disorders in children after covid-19 pandemic. Indeed, results also disclose numerous factors such as infrastructural conditions, greenery stock, safety measures, children's activities and communityparticipation in the community parks. The novelty of the study will help public health experts, psychologists, urban planners, environmentalists, policymakers, public representatives to take an ecofriendly sustainable development plan, thereby fostering a positive impact on children’s holistic development. Furthermore, this study provides some recommendations to increase the overall health conditions of the park’s children's zone.